2012
DOI: 10.1155/2012/921653
|View full text |Cite
|
Sign up to set email alerts
|

Redox Regulation of Calcium Signaling in Cancer Cells by Ascorbic Acid Involving the Mitochondrial Electron Transport Chain

Abstract: Previously, we have reported that ascorbic acid regulates calcium signaling in human larynx carcinoma HEp-2 cells. To evaluate the precise mechanism of Ca2+ release by ascorbic acid, the effects of specific inhibitors of the electron transport chain components on mitochondrial reactive oxygen species (ROS) production and Ca2+ mobilization in HEp-2 cells were investigated. It was revealed that the mitochondrial complex III inhibitor (antimycin A) amplifies ascorbate-induced Ca2+ release from intracellular store… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…In addition to their metabolic and apoptotic roles, mitochondria also serve as a major hub of cellular Ca 2+ homeostasis. Indeed, mitochondrial Ca 2+ homeostasis is fundamental for a wide range of cellular activities, such as control of oxidative phosphorylation [98,99], modulation of cytosolic calcium signals [100], cell death [101], secretion [102,103] and reactive oxygen species (ROS) production in cancerous cells [104]. Intra-mitochondrial Ca 2+ controls energy metabolism by enhancing the rate of NADH production by modulating critical enzymes, such as those of the tricarboxylic acid (TCA) cycle and fatty acid oxidation [105,106], linking glycolysis to the TCA cycle [107] (Fig.…”
Section: Vdac1 As a Ca 2+ Transportermentioning
confidence: 99%
“…In addition to their metabolic and apoptotic roles, mitochondria also serve as a major hub of cellular Ca 2+ homeostasis. Indeed, mitochondrial Ca 2+ homeostasis is fundamental for a wide range of cellular activities, such as control of oxidative phosphorylation [98,99], modulation of cytosolic calcium signals [100], cell death [101], secretion [102,103] and reactive oxygen species (ROS) production in cancerous cells [104]. Intra-mitochondrial Ca 2+ controls energy metabolism by enhancing the rate of NADH production by modulating critical enzymes, such as those of the tricarboxylic acid (TCA) cycle and fatty acid oxidation [105,106], linking glycolysis to the TCA cycle [107] (Fig.…”
Section: Vdac1 As a Ca 2+ Transportermentioning
confidence: 99%
“…A possesses both pro-oxidant and anti-oxidant properties (42)(43)(44)(45)(46)(47)(48)(49)(50). Although the preventive anti-cancer effect of A results from its anti-oxidant properties (42), previous in vitro studies and mouse models have demonstrated that A is able to inhibit cell proliferation in various types of cancer due to its ability to induce the production of H 2 O 2 (43-49) without being toxic to non-cancerous cells (43,50).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, elevated levels of reactive oxygen species (ROS) due to hydrogen peroxide formed, causes the toxicity to cancer cells. Induction of apoptosis, 27 autophagy, 26 impairment of mitochondrial structure, 28 and Ca 2+ release from mitochondria, 29 was concluded to be a consequence of increase in ROS production, upon exposure to vitamin C in high doses.…”
Section: Introductionmentioning
confidence: 99%